2019
DOI: 10.1111/joms.12542
|View full text |Cite
|
Sign up to set email alerts
|

Packs, Troops and Herds: Prosocial Cooperatives and Innovation in the New Normal

Abstract: Prosocial organizations are emerging to tackle the effects of a New Normal. As they navigate its fragile and liquid institutional membranes, they prioritize cooperative forms of governance. These forms allow for collaboration and democratic decision‐making necessary for the development of innovative solutions in this new context. At the same time, the high coordination costs of cooperatives lead to significant market pressures. Therefore, understanding when and under what conditions these new cooperatives inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 96 publications
(133 reference statements)
0
31
0
1
Order By: Relevance
“…Latin-America has only recently allowed the formalization of "for-benefit enterprises", led by Argentina and Colombia. Despite having a very active social sector (Muñoz et al, 2019), Chile (at the time of this writing) has not agreed on relevant legislative and regulative arrangements to support its social enterprises and social entrepreneurs. The first, and only so far, government support program for social ventures including impact measurement was only launched in August 2018 (Corfo, 2018), which only supports six incubators and 40 social entrepreneurs.…”
Section: A Nascent Social Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…Latin-America has only recently allowed the formalization of "for-benefit enterprises", led by Argentina and Colombia. Despite having a very active social sector (Muñoz et al, 2019), Chile (at the time of this writing) has not agreed on relevant legislative and regulative arrangements to support its social enterprises and social entrepreneurs. The first, and only so far, government support program for social ventures including impact measurement was only launched in August 2018 (Corfo, 2018), which only supports six incubators and 40 social entrepreneurs.…”
Section: A Nascent Social Sectormentioning
confidence: 99%
“…This is in line with Barman and Maclndoe's (2012) approach in dealing with the complexity of outcome measurement. Our study focuses on the nascent social sector in Chile (Muñoz, Kimmitt & Dimov, 2019), where we surveyed 152 social entrepreneurs. Using configurational comparative methods, we analyzed combinations of nine internal and external factors that might enable SIM formalization.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the more extreme populist groups have even questioned the societal value or legitimacy of the private firms with a for‐profit objective, with an increasingly positive reception among parts of the population in some countries. In turn, the preference for the development of more ‘social’ forms of organizations, having broader non‐profit objectives as cooperatives or family business, has grown (Munoz et al, 2020).…”
Section: A Central Strategic Challenge In the New Normal: Globalizatimentioning
confidence: 99%
“…The second paper, by Munoz et al (2020), examined the relationship between prosocial cooperatives (co‐ops) and innovation in the New Normal environment. The authors identified three cooperative forms of governance: The attention pack, the eclectic troop, and the wondering herd, that allow for collaboration and more democratic decision‐making necessary for the development of innovative solutions in the faster moving New Normal landscape, characterized by vastly improved communication and collaboration technologies.…”
Section: Articles In This Special Issuementioning
confidence: 99%
“…In addition, the pursuit of a high level of originality requires a shift to more individualistic tendencies (Munoz et al, 2020 ) and deviation from routines and the status quo (Zhou and George, 2001 ; Anderson et al, 2014 ). However, individuals with prosocial motivations are more likely to think from the perspectives of others and deviate less from the routine (Beersma and De Dreu, 2005 ), which may limit their divergent thinking and lead to cognition closure (Miron-Spektor and Beenen, 2015 ).…”
Section: Introductionmentioning
confidence: 99%